Symbol Behind The Sign: Linguistic Landscape In Surakarta, Indonesia - et. al, Dwi Purnanto, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the frequency, form, and informational-symbolic functions of texts in public spaces, in Surakara City, Indonesia, using the Linguistic landscape approach. Data were collated from 292 photo samples from five subdistricts in Surakarta, Indonesia. The interviews were conducted with target reader to see their perception of language use in public space. The results showed that five languages were used in text found in public spaces, namely Indonesian, Javanese, English, Arabic, and Japanese. Furthermore, the Indonesian was found to be the most dominant, followed by Javanese and English. Indonesian dominates the monolingual pattern, while its combination with Javanese dominates the bilingual pattern. Indonesian and Javanese symbolizes the language policy factors and the demographic strength of language speakers, while English displays a modern, global and exclusive image. Furthermore, Arabic shows a symbol of Islam, while Japanese strengthens the global capitalism symbol. The findings of the research are useful for providing an overview of the sociolinguistic situation of language use and the application of language policies in public space. These studies presently show gaps, especially in the case of data from various domains, such as government, education, health, and commerce. This research attempts to portray the Linguistic Landscape in Surakarta City from various domains left out in previous studies. This study provides a complete analysis of the linguistic cityscape in Linguistic landscape on available domains in Surakarta, Indonesia.